THE ENFORCEMENT OF FINAL ADMINISTRATIVE COURT JUDGMENTS: A COMPARATIVE STUDY BETWEEN INDONESIA AND JAPAN - David Boy Sumurung Silaban; Tunggul Anshari Setia Negara; Ngesti Dwi Prasetyo (CV. RADJA PUBLIKA, 2025)
The principle of fair law enforcement is a manifestation of the state adhering to the conception of the rule of law (rechtsstaat) as the ideal of the nation. This makes the Indonesian judiciary have an important role and the principles of simplicity, quick and low cost as mandated by the 1945 Constitution and Act no 48 of 2009 concerning Judicial Power. Enforcement of material law cannot be separated from enforcement of formal law, because both run with the aim of realizing a sense of justice for the community. Likewise, the enforcement of judicial decisions: which is a law that must be implemented by the Parties in dispute in it; must be realized for the sake of justice for the entitled Parties. Statistical data reveals that administrative court decisions are often not implemented by administrative agencies/officials. A comparison of the decision execution system between Indonesia and Japan provides an interesting insight into how the two countries, which have different historical backgrounds and judicial systems, enforce the law and execute decisions. This journal focuses on how the policies of the Administrative Court in Indonesia and the Japanese judiciary in executing Inkracht judgments. This analytical comparative study is expected to be a vehicle for scientific and practical exploration related to the fulfillment of rights and obligations for Parties in court disputes. The method used in this research is normative research method with conceptual approach and statutory approach. Some data and statistics from reliable sources are presented as facts that will be analyzed in this journal article..